Translation Strategies of Taboo Words in Christina Lauren’s “Beautiful Bastard” Novel From English Into Indonesian - Ni Putu Triska Riana Dewi; Ida Ayu Made Puspani; I Wayan Mulyawan (Research and Community Services Institutes of Udayana University, 2022)
This study is entitled Translation Strategies of Taboo Words in Christina Lauren’s “Beautiful Bastard” from English into Indonesian. This study at to find the types of taboo words and the translation strategies applied in translating the taboo words. The data were collected through the documentation method of the novel entitled Beautiful Bastard by Christina Lauren and its Indonesian version translated by Ine Milasari Hidajat under the same title. Then the data were analysed in a descriptive qualitative approach. Finally, the analysis was conducted by applying Wardhaugh’s (1986) theory of taboo words and translation strategies proposed by Davoodi (2009). The results showed that there were 140 data of taboo words were appeared in the novel. All kinds of taboo words, according to Wardhaugh (1986), appeared in the novel. Those are sex, death, excretion, bodily function, religiously matters, mother in law and animals. The most frequent type is linked to the sex term, while the least is mother in law. As for the translation strategies, each type of strategy proposed by Davoodi (2009) was found in the novel. They were censorship substitution, taboo for taboo and applying euphemism. Taboo for taboo was the most common strategy used by the translator, whereas the translation by applying euphemism was the least common strategy.